2015
DOI: 10.5812/ircmj.17(4)2015.26006
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effects of Oligonol, Acupuncture and Quantum Light Therapy on Chronic Nonbacterial Prostatitis

Abstract: Background:Chronic Nonbacterial Prostatitis (CNBP) is a condition that frequently causes long-term pain and a significant decrease in the quality of life.Objectives:The present study aimed to examine the analgesic effects of oligonol, acupuncture, quantum light therapy and their combinations on estrogen-induced CNBP in rats.Materials and Methods:This experimental study was conducted in Edirne, Turkey, using a simple randomized allocation. A total of 90 adult male Wistar rats were randomized into 9 groups of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Weight difference between the normal and E2 induced prostatitis groups, however, has already been reported in previous studies. These studies suggest that E2 may be causative or that prostatitis itself may play a role in such reduction in body weight [20, 21]. In our study, positive and the KRG groups also showed weight loss, which is E2 or prostatitis.…”
Section: Discussionsupporting
confidence: 60%
“…Weight difference between the normal and E2 induced prostatitis groups, however, has already been reported in previous studies. These studies suggest that E2 may be causative or that prostatitis itself may play a role in such reduction in body weight [20, 21]. In our study, positive and the KRG groups also showed weight loss, which is E2 or prostatitis.…”
Section: Discussionsupporting
confidence: 60%
“…The results of this study showed that 2% paid attention to patients' information and 31% considered physician's information and 67% considered drug information. This study showed that more efforts are needed for improving the quality of prescriptions (17). In 1386, Moatar et al evaluated the general skills of last year medical students from their own point of view.…”
Section: Advances In Bioscience and Clinical Medicinementioning
confidence: 98%